Growth, Water Relation, Yield and Crop Quality of Arabica Coffee in Response to Water Stress and Deficit Irrigation. - Gessese, Tesfaye Shimber (2006)
Coffee (Coffea Arabica L.) is the single most important commodity crop that comes after petroleum in the world market. It plays a significant role in the economy of Ethiopia, contributing over 60% of the nation's foreign exchange earnings, 30% of the government's direct revenue, 8% output of the agricultural sector and 4% of the gross domestic production. In spite of the importance of the crop in the country's economy, its average national yield is very low primarily because of traditional production technologies. Apart from hereditary characteristics of the trees, seasonal water stress and recurrent drought are among the major factors which account for low yields of the crop in most coffee growing regions of the country. In the present study, attempt was made to identie water stress tolerant Arabica coffee cultivars and deficit irrigation practices that could improve growth, yield, quality and water use efficiency of the crop under both protected environment and field condition in Ethiopia. Both rain shelter and field experiments were carried out in a randomized complete block design with three replications in the rain shelter and four replications in the field. In the first rain shelter ~EWSTAWUN %TAN MJU- SAMAD UWEfirn m MAww than NDI for coffee production particularly in areas where water is scarce and dry spells are prolonged. On the other hand, the effect of supplemental deficit irrigation on plant water relations, crop yield and quality was studied in the field using young coffee stands of three cultivars (F-59, 74110 and 75227). Two irrigation treatments, namely, supplemental full irrigation (SFI) and supplemental deficit irrigation (SDI), applied in the conventional way, were compared against rain fed (RF) control. SF1 consistently increased soil moisture content, leaf RWC and g, during the dry period, but there was no difference between the treatments in the main wet season. Besides, SF1 significantly increased coffee yield, but the difference between SF1 and SDI was not significant and yet SDI had 21 - 24% yield advantage over the RF treatment. On the other hand, overall quality of coffee beans was considerably increased by SDI and RF treatments. Therefore, SDI seems to be more effective than SF1 and it can be used as an option next to PRD for coffee production in drier areas. study, twenty four known cultivars, which are indigenous to the country, were subjected to a soil drying treatment to identify those tolerant genotypes. Variations among the cultivars for mean stress scores, rate of recovery from drought, root to shoot ratio, concentration of inorganic solutes (K, Ca and Mg) in leaves, specific leaf area and survival rate showed that some of the genotypes, such as 741 10, 741 12 and 8/85, were less sensitive to water stress at seedling stage. On the other hand, in an experiment where three irrigation regimes (well watering, WW, normal deficit irrigation, NDI, and partial root zone drying, PRD) were studied on cultivar F-59 grown in a rain shelter, it was found that NDI and PRD reduced shoot growth, total dry matter production, dry weights of leaves, stem and roots, leaf relative water content (RWC) and stomata1 conductance (g,), but increased root to shoot ratio and irrigation water use efficiency (IWUE) of coffee seedlings. Therefore, it was concluded that PRD is an effective deficit irrigation practice to increase I'WUE and decrease irrigation water requirement by 50% without substantial adverse effects on plant growth and development, and it could be practically advantageous in coffee nurseries especially in areas of water scarcity and prolonged drought periods. The same study was carried out in the field to determine the effect of PRD on plant water relations and crop yield and quality of Arabica coffee. Results of the field experiment also indicated that leaf RWC, g,, h i t growth rate and some yield components were reduced by both PRD and NDI. However, the difference between WW and PRD was not significant for crop yield and yet PRD resulted in over 41% more IWUE than the WW treatment, reduced the amount of irrigation water by 50% and considerably improved both raw and liquor quality of coffee beans. Hence, it was concluded that PRD can be a feasible irrigation strategy, which can save irrigation water, increase IWUE and maintain crop yield, and it appears to be more advantageous